What skills should a future teacher develop during their time at university? Perception of student teachers on ente- ring their initial teacher training programmes - Quiroga Lobos, Marta; Soto Lillo, Paula; Medina Pérez, Jessica (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The aim was to identify the skills that good teachers should have from the perception of future teachers. A total of 1047 responses from student teachers entering university in 2021 and 2022 were analysed. The results show that future teachers consider the development of ethics and responsibility, empathy and managing student behaviour in the classroom as the most important skills to develop at university. It is concluded that having interaction skills is more important than conceptual mastery to be a good teacher according to this group of preservice teachers.